New genetic diversity for endangered bottlenose dolphin subspecies along the Argentine coast - Loizaga de Castro, Rocio (2020)
This study analyzed mtDNA sequences of two bottlenose dolphin subspecies found along the northern Patagonian coast, Argentina: the endangered Tursiops truncatus gephyreus and the data deficient Tursiops truncatus truncatus. Three haplotypes were recovered from nine samples. The most frequent haplotype represented the coastal morph, also two haplotypes showing falcate dorsal fin, a characteristic describing the oceanic morph. This finding suggests that both morphs may exist in sympatry in Argentina. Furthermore, sampling was extended beyond the species´ previously known range, including individuals as far as seven hundred kilometers to the south. Therefore, new genetic data, despite being preliminary, hint at an unexpectedly higher genetic diversity of matrilines than previously anticipated.